Prevalence of Skin Disorders in Kintamani Dog - Vidia Tiara Timur, Ni Putu; Sisyawati Putriningsih, Putu Ayu; Puja, I Ketut (Veterinary Science and Medicine Journal; Vol 3 No 1 (2015), 2015)
The aim of this study was to determine the prevalence of skin disorders in Kintamani Bali dog from 2009 to2013 using an observational study with purposive sampling technique. The data was taken from the patientrecords in veterinary clinics in Badung Regency, Gianyar Regency and Denpasar City which thereafteranalyzed descriptively. From 475 dogs, 99 dogs (20.8%) were infected by skin disorder. Skin disordersobserved in this study was caused by parasites (15.2%), fungus (2.1%), virus (2.1%) and bacteria (1.5%).The case of skin disorders frequently occurred in the dry season (53.1%) than in rainy season (46.9%), witha variation in age from 3 months to 12 years old.
Keywords: prevalence, skin disorders, Kintamani dog